PERAN STRATEGIS PENGEMBANGAN SDM DALAM MENCAPAI KEUNGGULAN BERSAING - Nur Syafira Ramona; Nur Afifah Lutfina; Sarah Nursa’diah Hidayat; Silfia Rachim; Mira Veranita (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
In the era of globalization and rapid technological advancement, human resource development (HRD) plays a strategic role in achieving competitive advantage for organizations. This study uses a qualitative descriptive approach through literature review to explore the role of HRD strategies in enhancing employee competencies, loyalty, and an innovative work culture that supports organizational performance. Findings indicate that integrating HR functions into business strategies, along with leveraging technologies such as AI and VR, strengthens the effectiveness of employee training and development. Planned and continuous HR development not only improves individual quality but also enhances organizational competitiveness in facing global challenges. Therefore, HR development should be prioritized strategically in organizational planning to support sustainable growth and business continuity.